Analysis of The Ability to Understand Mathematical Concepts in Terms of Students' Confidence in Blended Learning (Department of Mathematics, Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the effectiveness of the ability to understand mathematical concepts in Blended Learning and to determine the pattern of ability to understand mathematical concepts in terms of students' confidence in Blended Learning. The research method used is experimental research with a sequential explanatory strategy. The population of this study was class VII students of Junior High School 28 Semarang for the academic year 2020/2021, with the research sample being class VII A (experimental class) and class C (control class); sampling was done using a simple random sampling technique. Subjects to obtain quantitative data, namely students from the experimental class, were selected by nine students based on the grouping of the results of the self-confidence questionnaire. The data obtained from the calculation of quantitative data, namely the results of the study, show that Blended Learning is effective for improving students' understanding of mathematical concepts. In the analysis of test results and interviews, triangulation was carried out, namely based on the level of student confidence showing the pattern of students' ability to understand mathematical concepts, namely students with high levels of confidence had good mathematical concept skills, those with moderate confidence levels had sufficient mathematical concept understanding abilities, while students with low self-confidence, lack of mastery of the ability to understand mathematical concepts they have. It can be concluded that the higher the students' self-confidence, the more confident they will be in solving problems with their ability to understand mathematical concepts.